Effect of Psychological Capital of Volunteers on Volunteering Behavior: The Chained Mediation Role of Perceived Social Support and Volunteer Motivation - Xu, Li ping; Liao, Jin bao; Wu, Yu shen; Kuang, Hong da (Frontiers in Psychology, 2021)
This study explored the role of perceived social support and voluntary motivation in the effect of volunteers’ psychological capital on volunteering behavior. A sample of 1165 volunteers who were registered in the China Voluntary Service Information System was investigated using a self-reported questionnaire, showing that volunteers’ psychological capital, perceived social support, voluntary motivation, and volunteering behavior were significantly and positively related to each other. Volunteers’ psychological capital affected volunteering behavior not only directly, but also indirectly through the mediating role of voluntary motivation. Moreover, perceived social support and voluntary motivation also played a chain role in the relationship between volunteers’ psychological capital and volunteering behavior. Therefore, increasing volunteers’ psychological capital should promote their perceived social support and inspire voluntary motivation, in turn affecting their volunteering behavior.